2017
DOI: 10.1111/anu.12645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean meal replacement with fermented soybean meal on growth, serum biochemistry and morphological condition of liver and distal intestine of Florida pompanoTrachinotus carolinus

Abstract: This study evaluated the suitability of commercially produced fermented soybean meal (FSBM) known as PepSoyGen™, in a plant-based diet for Florida pompano, Trachinotus carolinus fingerlings. An 8-week growth trial was conducted to evaluate the effect of four isonitrogenous and isolipidic diets containing 0, 206, 309 and 410 g/ kg FSBM, replacing approximately 0%, 50%, 75% and 100% SBM (designated as Basal, FSBM 50, FSBM 75 and FSBM 100, respectively) on growth performance, body composition, serum biochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…Recent work with various advanced soy products, such as fermented soybean meal (FSBM) and enzyme‐treated soybean meal (ESBM), seems promising due to their ability to improve nutritional value of soy protein and substitute for the use of animal meal in fish diet formulation (Barnes, Brown, Bruce, Sindelar, & Neiger, ; Lim & Lee, ; Novriadi, ; Novriadi, Rhodes, Powell, Hanson, & Davis, ). Fermentation processes that allow microorganisms to degrade macromolecules to low molecular weights have been reported to have numerous benefits, including the degradation of soy immunoreactivity (Song, Frias, Martinez‐Villaluenga, Vidal‐Valdeverde, & de Mejia, ), lower levels of ANFs (Lim et al, ; Mukherjee, Chakraborty, & Dutta, ), and improvement of the nutritional quality and fibrinolytic enzyme activity of the commercial SBM (Bi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work with various advanced soy products, such as fermented soybean meal (FSBM) and enzyme‐treated soybean meal (ESBM), seems promising due to their ability to improve nutritional value of soy protein and substitute for the use of animal meal in fish diet formulation (Barnes, Brown, Bruce, Sindelar, & Neiger, ; Lim & Lee, ; Novriadi, ; Novriadi, Rhodes, Powell, Hanson, & Davis, ). Fermentation processes that allow microorganisms to degrade macromolecules to low molecular weights have been reported to have numerous benefits, including the degradation of soy immunoreactivity (Song, Frias, Martinez‐Villaluenga, Vidal‐Valdeverde, & de Mejia, ), lower levels of ANFs (Lim et al, ; Mukherjee, Chakraborty, & Dutta, ), and improvement of the nutritional quality and fibrinolytic enzyme activity of the commercial SBM (Bi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese seabass fed with a full plant protein diet decreased blood glucose level [38]. However, there was no significant difference in blood glucose of Trachinotus carolinus fed with soybean meal diet was observed [37,39]. Our study revealed that high level of rapeseed meal could decrease blood glucose, which suggests that glucose uptake into tissues and glucose phosphorylation levels might be improved.…”
Section: Discussionmentioning
confidence: 55%
“…Previous findings when fish fed with various levels of ESBM (102.2–148 g/kg) to replace 150 g/kg dietary PBM supplemented with squid hydrolysates and squid meal did not show any clinical differences for total protein, albumin, glucose, cholesterol, bile acids, ALP, AST and ALT enzyme activities among the dietary treatments (Novriadi, Spangler et al, ). Additional studies with the replacement of conventional SBM with various level of commercial FSBM also did not show any significant differences in all observed serum and enzyme activities parameters (Novriadi, Rhodes et al, ). Our results in the present study largely confirm the PBM replacement study where the various replacement of dietary FM with ESBM did not cause any significant effect on the total protein, albumin, ALP, ALT, AST, glucose and bile acids contents.…”
Section: Discussionmentioning
confidence: 86%
“…Samples were dehydrated through a standard ethanol series to 100%, embedded in paraffin wax and sectioned at 4 µm intervals for staining with Haematoxylin‐Eosin (H&E) stain (Merck, Darmstadt, Germany). Double blinded evaluation with a grading system of 1 (healthy) to 5 (degraded) was used to evaluate the distal intestine condition according to Novriadi, Rhodes et al (). The following parameters were evaluated for distal intestine analysis: the number of goblet cells (GC), level of cellular infiltration (CI) and thickness of the lamina propria within the intestinal folds (WLP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation